Correlation and Path Coefficient Analysis of Yield and Agronomic Characters among some Maize Genotypes and Their F1 Hybrids in a Diallel Cross - Abdulkhaleq, Dana Azad; Tawfiq, Sherwan Ismael (Sulaimani Journal for Pure and Applied Sciences, 2014)
Grain yield in maize (Zea mays L.) can be improved by understanding the interrelationships among yield, yield components, vegetative growth, and growth period. The objective of this study was to determine the relationship among some of the most important growth and yield traits by using correlation coefficient and path coefficient Data were obtained to from 25 F1 hybrids including reciprocals in a diallel mating design. Kernels yield plant-1 had positive and significant correlation with No. of kernels row-1, kernels weight ear-1 at both locations, and with cob weight at Kanipanka location, while has no significant correlation with the other characters. Path analysis indicated that kernel weight ear-1, No. of ears plant-1, and No. of kernels row-1 showed high direct effect on kernel yield plant-1 at Kanipanka location, while at Qlyasan location No. of kernel row-1, 300-kernel weight, No. of ears plant-1, and kernel weight ear-1 showed the high direct effect on kernel yield plant-1, these traits can be considered as principal yield component and the breeder can be use these as selection criteria for kernel yield improvement.
Keywords: Maize; Zea mays L; Correlation coefficient; Path coefficient analysis